Animal Kingdom - Burnie, David; Clarke, Barry; McCarthy, Colin; Mound, Laurence; Parker, Steve (New York : DK Publishing, Inc., 2004)
A collection of books, previously published separately, from the lavishly illustrated DK Eyewitness series, describing a wide variety of animals, their characteristics, behavior, and habitats, as well as interesting miscellaneous facts about each.
Fish -- Amphibian -- Reptile -- Insect -- Bird -- Mammal.
Includes index.
5-8
Keywords: Animals -- Miscellanea; Zoology; Fishes; Amphibians; Reptiles; Insects; Birds; Mammals